Impact of Paediatric Versus Adult Care Setting on Health Care Utilization in Adolescents With Inflammatory Bowel Disease. Issue 3 (September 2019) - Bottema, Renske W.B.; de Vries, Han; Houwen, Roderick H.J.; van Rheenen, Patrick F.
ABSTRACT: Objective: Paediatric-onset inflammatory bowel disease (IBD) is different from adult-onset IBD with respect to disease severity and its effect on growth and development. Care of paediatric IBD patients in some countries is dispersed among paediatricians and adult care providers, which may result in different outcomes. This study aims to assess the effect of care setting (paediatric vs adult-oriented) on health care utilization in adolescent IBD patients. Methods: This is a Dutch population-based cohort study based on an insurance claims database covering 4.2 million insurees (approximately 25% of the Dutch population). We identified IBD patients ages 16 to 18 years and followed them until the age of 19 years or transfer to adult care, whichever came first. We categorized patients according to care setting: paediatric versus adult-oriented. We defined outcomes as corticosteroid use, IBD-related hospital admission, IBD-related surgery, and biological use. We estimated Cox proportional hazards regression models to control for confounding by indication. Results: Among 626 patients, 380 (61%) were in paediatric and 246 (39%) in adult-oriented care. In paediatric care, patients were less likely to be treated with corticosteroids (hazard ratio [HR] 0.72, 95% confidence interval [CI] 0.52–0.99) or biologicals (HR 0.57, 95% CI 0.34–0.97), and had fewer IBD-related hospital admissions (HR 0.58, 95% CI 0.37–0.92). Conclusion: In a large and representative community cohort of adolescents with IBD, treatment in paediatric care setting was associated with significantly lower steroid and biological use, without increase in hospital admissions. These results might be used to optimize clinical care for adolescents with IBD. Abstract : Supplemental Digital Content is available in the text